Komunikasi Pemasaran Media Sosial Instagram @carameleatery - Anandia Ekklesia Gabriella; Farid Farid (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
This culinary cafe business is getting crowded thanks to Instagram trends. The concept of